Attitudes to acute pain and the use of pain assessment scales among Spanish small animal veterinarians - Menéndez, Sandra; Cabezas, Miguel Angel; Gomez de Segura, Ignacio A. (Frontiers in Veterinary Science, 2023)
Evaluation of acute pain in dogs and cats is the basis for an appropriate treatment and improved well-being. The difficulties involved in pain assessment pose a challenge for veterinarians, and recent findings indicate that the most effective tools available-validated pain assessment scales-may not be widely utilized.Objectives: This study aimed to characterize the level of concern among Spanish veterinarians regarding acute pain in companion animals. Additionally, it sought to determine whether this concern correlates with the utilization of optimal assessment tools.Methods: A survey was conducted to explore Spanish veterinarians' attitudes toward pain and its assessment. The survey was distributed through two most prominent small animal veterinary associations, the Spanish association for veterinary anaesthesia and analgesia, as well as key industry players committed to proactive pain management. Descriptive analysis of the collected data was performed using Excel and SPSS.Results: A total of 292 veterinarians participated in the study. A high level of concern regarding pain in dogs and cats was determined where 44% of surveyed veterinarians assessed pain in all patients.Despite an awareness of validated pain scales, only 28% used them. The preferred scales were the Glasgow CMPS for dogs (94%) and the Feline Grimace Scale for cats (93%). Among respondents who do not use these validated tools, there was a considerable interest in incorporating these scales into practice (85%) and considered lack of training was the most relevant issue (32%). Other challenges to scale utilization were identified, including constraints related to time, staffing, and the need to establish a habit.Conclusions and Relevance: Spanish small animal veterinarians demonstrate a strong awareness to pain in their patients and employ various methods for pain assessment. However, a limited use of validated tools was identified and likely attributed to challenges such as a lack of established routine, time constraints, insufficient personnel, and, notably, a knowledge gap among veterinarians who do not employ pain assessment scales. The most commonly used scales are the Glasgow CMPS for dogs and the FGS for cats. Overall, these results suggest a window of opportunity for the implementation of training programs in small animal pain assessment at a national level.